Deliverable 1.1 Initial Requirement Report - Buch, Erik; Tjernström, Michael; Quegan, Shaun; Ahlstrøm, Andreas Peter; Heygster, Georg; Soltwedel, Thomas; Danielsen, Finn; Ottersen, Geir; Johannessen, Truls; Sandven, Stein (Zenodo, 2017)
The detailed analysis of phenomena and observation requirements for the Arctic region given in this report reveals the following conclusions: • The Arctic is a region very sensitive to environmental changes. There is a very close interrelation and delicate balance between the five thematic areas investigated(atmosphere, terrestrial, cryosphere, sea ice and ocean),especially in relation to solar energy and radiation budget and hydrological cycle. This has a great impact on physical, chemical and biological processes in the area. • Due to the hostile environment, there is a great lack of basic observations in the Arctic,that can support scientific understanding of key processes. Most of the existing data are collected via time limited research projects. This lack of process knowledge is reflected in big errors in forecasting models –operational as well as climate. • It is therefore crucial to establish a sustained Integrated Arctic Observing System,that in the short time frame can increase fundamental scientific understanding of the complex and sensitive Arctic environment and in a longer time frame can secure a robust basis for decision making to the benefit of the people living in the Arctic, the environment, the broader international society, and commercial activities. • It is foreseen that a future Arctic observation system will rely heavily on satellite observations supplemented by more traditional in-situ platforms. Especially the ocean will use several other platforms such as ships, profiling floats, gliders, moorings, AUVs etc. to monitor the interior of the Arctic Ocean. • In all countries around the Arctic, there are community based observing systems that represent a strong potential for further development. Existing activities shall form part of the natural basis for a future more intensive and integrated sustainable Arctic Observing System. • A stakeholder workshop was held in Brussel on 5 May, organised by EuroGOOS, where status and challenges regarding development of Arctic Observing Systems were ...